Theoretical Study of the Transfer Rate Constant for Electron at Metal /Liquid Interface - Hadi J. M. AL-Agealy (University of Thi-Qar Journal of Science, 2019)
A quantum transport in Cu/ TCNQ molecule liquid interface, the influence of reorganization energy coupling matrix element, and temperature are studied. For the tunneling transport description, reorganization energy and rate constant of electron transfer of Cu/ TCNQ molecule liquid interface system are calculated and the transmission through interface are examined. A theoretical model based on the quantum system is depending to study the transfer across Cu and TCNQ molecule. While on the interface system, classical reorganization energy equation using to evaluate the electrons energy to reorientation before transfer, the transition rates are calculated using quantum transport formalism. Our results data show that the rate constant increases with the increasing of the coupling coefficient and temperature, and decreasing of the reorganization energy .Theoretical study for transfer rate constant, electron transfer, metal/liquid interface.